Wind-induced sediment resuspension as a potential factor sustaining eutrophication in large and shallow Lake Peipsi - Tammeorg, Olga; Niemistö, Juha; Möls, Tõnu; Laugaste, Reet; Panksep, Kristel; Kangur, Külli (Aquatic sciences, 2013)
Using sediment traps, we aimed to elucidate the temporal and spatial variations in sediment fluxes in large and shallow Lake Peipsi, over the May to October 2011 period, and analyze the factors behind those variations. The effects of weather factors (mean and maximum wind velocity, water level and water temperature) on sediment resuspension and the concentrations of suspended solids (SS), total phosphorus (TP), soluble reactive phosphorus (SRP), and chlorophyll a (Chl a ) were investigated. Moreover, the internal loading of TP due to sediment resuspension was determined. The sediment resuspension rates were significantly higher in the shallower waters than in the deeper parts of the lake. Resuspension was a major factor in sedimentation dynamics of the lake, which is presently subject to eutrophication. The rates of sediment resuspension followed the same pattern as gross sedimentation during the study period, and their respective values differed significantly between sampling dates. The highest resuspension rates were observed in September (mean 55.4 g dw m −2 day −1 ), when the impacts of wind events were particularly pronounced. Weather factors that were recorded approximately 2 weeks before water and sediment sampling affected the gross sedimentation and sediment resuspension. The water quality variables of SS, TP, SRP, Chl a were similarly affected. During the study, TP concentrations of the water were mainly determined by the resuspension of sediments containing a large pool of organic material. Although internal loading of TP due to resuspension was several times greater than external loading, external loading determines the amount of phosphorus that enters the lake and can be resuspended.